The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1073/pnas.95.24.14278
|View full text |Cite
|
Sign up to set email alerts
|

Physical interaction between components of DNA mismatch repair and nucleotide excision repair

Abstract: Nucleotide excision repair (NER) and DNA mismatch repair are required for some common processes although the biochemical basis for this requirement is unknown. Saccharomyces cerevisiae RAD14 was identified in a two-hybrid screen using MSH2 as ''bait,'' and pairwise interactions between MSH2 and RAD1, RAD2, RAD3, RAD10, RAD14, and RAD25 subsequently were demonstrated by two-hybrid analysis. MSH2 coimmunoprecipitated specifically with epitope-tagged versions of RAD2, RAD10, RAD14, and RAD25. MSH2 and RAD10 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(70 citation statements)
references
References 59 publications
(74 reference statements)
1
66
1
2
Order By: Relevance
“…Msh2 −/− mice exhibit an increased predisposition to skin cancer in response to UVB exposure that is enhanced when mice are additionally defective for the NER Xpc gene (Meira et al, 2002). Interactions between scMsh2 and the NER proteins Rad2, Rad10, and Rad14 have been observed in co-immunoprecipitation experiments (Bertrand et al, 1998), and loss of MMR in human cells leads to a deficiency in transcription-coupled NER (Mellon et al, 1996). These and other studies point to a still poorly defined interaction between elements of these two excision repair pathways.…”
Section: Mmr and Dna Damage Signallingmentioning
confidence: 98%
“…Msh2 −/− mice exhibit an increased predisposition to skin cancer in response to UVB exposure that is enhanced when mice are additionally defective for the NER Xpc gene (Meira et al, 2002). Interactions between scMsh2 and the NER proteins Rad2, Rad10, and Rad14 have been observed in co-immunoprecipitation experiments (Bertrand et al, 1998), and loss of MMR in human cells leads to a deficiency in transcription-coupled NER (Mellon et al, 1996). These and other studies point to a still poorly defined interaction between elements of these two excision repair pathways.…”
Section: Mmr and Dna Damage Signallingmentioning
confidence: 98%
“…Thirdly, in strong support of the above, but using a different type of strand-specific DNA repair assay that measures the post-excision (gap-filling) steps of NER, it was subsequently demonstrated (i) that both hMLH1-and hMSH2-deficient human adenocarcinoma cells are impaired in TCNER of UV-induced CPDs at the active metallothionein locus (Leadon and Avrutskaya, 1997), and (ii) that hMSH2-(but not hMLH1-) deficient cells (Leadon and Avrutskaya, 1997) as well as MMR-deficient yeast (Leadon and Avrutskaya, 1998) are defective in transcriptioncoupled repair of oxidative DNA damage (presumably via base excision repair rather than nucleotide excision repair). Finally, a number of in vitro studies, e.g., including those based on the yeast S. Cerevisiae (Bertrand et al, 1998;Fleck et al, 1999;Kirkpatrick and Petes, 1997) as well as human cells (Wang et al, 1999), have revealed physical and functional interactions between components of the MMR and NER pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Conclusions and future perspective corrects lesions in the transcription template strand of RNA polymerase II-transcribed genes [65.] Although the mechanistic details of the involvement of MMR proteins in TCR are not known, specific interactions between MSH2 and NER proteins have been detected in yeast [66]. MSH2 contributes to the recognition of a stalled RNA polymerase on the transcription template strand at sites of DNA damage.…”
Section: Discussionmentioning
confidence: 99%